Mycoplasma pneumoniae attachment to WiDr cell cultures: competitive inhibition assays. - Chandler, D. K. (Yale Journal of Biology and Medicine, 1983)
Attachment of radiolabeled M. pneumoniae to human WiDr cell culture monolayers was dependent on the WiDr cell density and the concentration of M. pneumoniae. Saturation of confluent monolayers grown on 5 mm coverslips was attained with only 40 micrograms of M. pneumoniae protein. Preincubating the WiDr monolayers with unlabeled M. pneumoniae or with a protein-rich extract prepared from M. pneumoniae inhibited subsequent attachment of radiolabeled organisms. Attachment inhibition by the M. pneumoniae extract provided a quantitative assay for mycoplasmal binding components. Treatment of radiolabeled M. pneumoniae with orosomucoid, ceruloplasmin, and gangliosides inhibited attachment to WiDr cells. These sialoglycoconjugates may be structural analogues of the target cell receptor.